Network selection algorithm in heterogeneous wireless networks to minimize the maximum residual service time - Bai DU; Hong-yan LI; Yan LONG (Tongxin xuebao)
Due to the problem of how to select the most suitable access network for users at any time anywhere in heterogeneous wireless networks(HWN),a distributed algorithm to minimize the difference of residual service time between different access networks was proposed.The algorithm use the Lyapunov optimization to model the network and guarantee the stability of the network.Simulation results show that the proposed algorithm can decrease the rejection ratio and achieve a shorter queue length in access networks.